Dysregulation of decidual NK cell proliferation by impaired decidual cells: a potential contributor to excessive trophoblast invasion in placenta accreta spectrum - Liu, You-Zhen; Lin, Hsin-Hung; Wu, Meng-Shiue; Shih, Jin-Chung; Ling, Thai-Yen (Frontiers in Cell and Developmental Biology, 2025)
Aberrant interactions among decidual stromal cells, decidual natural killer (dNK) cells, and trophoblasts are implicated in placenta accreta spectrum (PAS) pathogenesis, though the underlying mechanisms remain unclear. This study investigates the relationship between defective decidualization of endometrial stromal cells and dysregulated dNK cell proliferation, which may contribute to excessive trophoblast invasion and the development of PAS. We established an in vitro system that mimics the decidual microenvironment to investigate these interactions. Maternal decidua-derived mesenchymal stem cells (MD-MSCs) from healthy pregnancies and PAS patients (PA-MSCs) were isolated and induced to undergo decidualization using hormonal and chemical stimuli. Peripheral natural killer (pNK) cells were then co-cultured with these MSCs to generate dNK-like cells. Cellular interactions among MSCs, dNK-like cells, and trophoblasts were evaluated using an in vitro co-culture system. Decidualization defects in PA-MSCs were marked by reduced morphological changes and dysregulated expression of decidual markers, potentially associated with estrogen receptor (ER) overexpression. Furthermore, both PA-MSCs and normal MD-MSCs similarly regulated trophoblast invasion, suggesting an indirect impact of impaired decidual cells on trophoblast behavior. Interestingly, decidualized MD-MSCs (De-MD-MSCs) showed the potential to induce the conversion of pNK cells into dNK-like cells, which displayed reduced cytotoxicity on trophoblasts and elevated KIR2DL4 expression. These dNK-like cells exhibited increased proliferation when co-cultured with PA-MSCs, enhancing trophoblast invasion and spiral artery remodeling. Conditioned medium derived from PA-MSCs-induced dNK-like cells demonstrated a higher capacity to promote trophoblast invasion in a dose-dependent manner. The abnormal proliferation of dNK cells induced by impaired decidual cells may contribute to the pathogenesis of PAS, providing valuable insights into its mechanisms and potential therapeutic interventions.